To borrow or not to borrow: Empirical evidence from the public debt sustainability of Pakistan - Wajid Islam; Junaid Ahmed; Naseem Faraz (Asian Development Bank Institute (ADBI), 2023)
This study aims to evaluate the public debt sustainability of Pakistan using the debt sustainability analysis (DSA) framework and fiscal reaction function (FRF). For the empirical analysis, it uses relevant important macroeconomic variables, such as public debt, external debt, primary balance, output growth, current account balance, and oil prices, over the period 1976-2021. The results of the DSA suggest that, at the 10% growth rate with a real interest rate lower than 10%, the public debt level can be brought under the 60% standard sustainable limit from the current 80% by the year 2030. Furthermore, the estimates of the FRF reveal no evidence of debt sustainability. Besides this, the COVID-19 pandemic is positively associated with the primary balance mainly due to the decrease in the primary balance from -3.5% in 2019 to -0.9% in 2020. This is expected as a large amount of debt relief was provided to Pakistan during this period. Overall, our findings indicate that, if the rapid debt accumulation trend continues, the country will be unable to bear such a hefty load of ballooning debt. Therefore, a strategy of continuing coordination of fiscal and monetary policy is crucial for robust growth momentum to keep the debt sustainable.
Keywords: H60; H63; H68; H69; 330; public debt; primary balance; current account balance; COVID-19